2023
DOI: 10.1507/endocrj.ej22-0521
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of neonatal hypoglycemia in neonates born to mothers with gestational diabetes

Abstract: Hypoglycemia is one of the most significant problems in neonates born to mothers with gestational diabetes (GDM). This study aimed to identify novel predictors of hypoglycemia in neonates born to mothers with GDM. A total of 443 term singleton infants from mothers diagnosed with GDM and cared for at Keio University Hospital between January 2013 and December 2019 were included in this study. Neonatal hypoglycemia was defined as hypoglycemia of less than 47 mg/dL at 1 or 2 or 4 h after birth, according to previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
(37 reference statements)
1
2
0
Order By: Relevance
“…We refrained from including plasma glucose values obtained from OGTT as a covariate due to uncertainties regarding measurement levels derived from different sampling medium and assay methods but adjusted for the mode of treatment initiated at diagnosis. A recent study concluded that third trimester HbA1c and hyperglycemia during labor were not predictors of neonatal hypoglycemia in offspring of mothers with GDM treatment, which is further corroborated by findings reported by others, 39,40 and the HAPO‐study showed no association between maternal glucose levels and neonatal hypoglycemia 1 . We lacked information regarding labor duration, intensity of fetal surveillance during labor, and the timing and duration of supplemental feeding which could provide insight into the mechanisms behind our results.…”
Section: Discussionsupporting
confidence: 85%
“…We refrained from including plasma glucose values obtained from OGTT as a covariate due to uncertainties regarding measurement levels derived from different sampling medium and assay methods but adjusted for the mode of treatment initiated at diagnosis. A recent study concluded that third trimester HbA1c and hyperglycemia during labor were not predictors of neonatal hypoglycemia in offspring of mothers with GDM treatment, which is further corroborated by findings reported by others, 39,40 and the HAPO‐study showed no association between maternal glucose levels and neonatal hypoglycemia 1 . We lacked information regarding labor duration, intensity of fetal surveillance during labor, and the timing and duration of supplemental feeding which could provide insight into the mechanisms behind our results.…”
Section: Discussionsupporting
confidence: 85%
“…Similar results (31.7%) were observed in a study conducted at a maternal and children's hospital in Najran, which stated that gestational diabetes increases hypoglycemia at birth [ 25 ]. A study conducted in Japan about risk factors for neonatal hypoglycemia and gestational diabetes mentioned that 45% of newborns developed neonatal hypoglycemia [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also required to consider that some newborns have high‐risk factors for hypoglycemia, and the relevant mechanisms are abnormal glucose‐related regulatory hormones and/or insufficient self‐storage, specifically divided into maternal factors, such as gestational diabetes and a history of prenatal high‐dose glucose infusion leading to increased insulin secretion in newborns, 15,26,27 and neonatal factors, such as prematurity, LGA, SGA 15,26 . The included guidelines all refer to the above‐mentioned high‐risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…| 45 specifically divided into maternal factors, such as gestational diabetes and a history of prenatal high-dose glucose infusion leading to increased insulin secretion in newborns, 15,26,27 and neonatal factors, such as prematurity, LGA, SGA. 15,26 The included guidelines all refer to the above-mentioned high-risk factors. In addition, attention needs to be paid to the screening of endocrine or metabolic diseases.…”
Section: Cps [15]mentioning
confidence: 99%